Authorship and the Narrative of the Self - Hartley, John (2013)
This chapter conforms to the plot scheme recommended by Frances Taylor Patterson, instructor of silent-movie photoplay composition at Columbia University in the 1920s, who summarized it as follows: Act I - get a man up a tree; Act II - throw stones at him; Act III - get him down. In this case, the "man" in question is "the author". This plot structure enables a conceptual and textual investigation of authorship under three headings: God is an Author (Shakespeare); No-one is an Author (Vogue); Everyone is an Author (Jefferson Hack). Authorship falters where a print publication can work at the top level of professional creativity and name-branded talent without needing the concept to organize the way that readers respond to the text. The chapter also talks about "narrative of the self" and the way that do-it-yourself publishing and social media have everyone responsible for participating in authorship © 2013 John Wiley & Sons, Inc.